Sistem Pendukung Keputusan Menentukan Kelanjutan Dan Kinerja Keuangan Pada Usaha Produksi Gas Menggunakan Metode Rasio Likuiditas - Nadia Pranata; Tiara Nur Safitri (Universitas Budi Darma, 2021)
In this case, the research conducted aims to determine the sustainability and financial performance of the gas production business. In this study also, the liquidity ratio method that can be used to find out these problems can be calculated through the current ratio, quick ratio, and cash ratio. By taking the data that has been obtained, it is the result of gas sales during October. By using this liquidity ratio method, the data that has been processed through the calculation of the current ratio, quick ratio, and cash ratio shows that business continuity and financial performance in this gas production business have a very important effect. Where the continuation of the business gets the calculation result >1, then this business is feasible to continue, and the financial performance with the income earned by this business per day until the end of October increases.